REMOVAL OF HARMFUL BLUE-GREEN ALGAE Microcystis spp. USING AGRICULTURAL AND AQUACULTURAL WASTE - Pongswat, Sirikae; Chaosuan, Natthaphon; Kapphimai, Watcharapol (Progress in Applied Science and Technology, 2017)
Eutrophication is an indicator of the decline of water quality and aquatic ecosystem changes. This problem occurs in the main water resources in Thailand and is getting more severe, particularly in fresh water. This research focused on using agricultural residues and aquacultural waste - rice straw and shrimp shells to eliminate dominant species of toxic algae Microcystis spp. in eutrophication. In the laboratory scale experiment, 5 groups of the two-substance mixture, including one controlled group were used. The ratios of the straw extracts and chitosan from shrimp shells mixture were 3:1, 2:1, 1:1, 1:2, and 1:3. The experiment result indicated that the mixture was effective in inhibiting the growth of toxic algae Microcystis spp. The different efficiency among the five groups was statistically significant at the level of .05. The best achievement was from the ratio of 1:2 group that the cell numbers (42.42x105cells/mL) were reduced to 3.98x105cells/mL and a reduction of chlorophyll a content from 1667.13 μg/L to 511.94 μg/L. This optimum mixture was then used in the field experiments, resulting in the inhibition of cell number and chlorophyll a at 76.97 and 46.51%, respectively. In addition, the amount of ammonia nitrogen (NH3-N), nitrate nitrogen (NO3-N) and orthophosphate (PO4-P) were reduced by 85.82, 51.67 and 36.36%, respectively.